PERIPHERAL RETINAL VASCULOPATHY IN COCKAYNE SYNDROME. Issue Volume 11:Issues 3(2017:Summer) (2017) - Trese, Matthew G. J.; Nudleman, Eric D.; Besirli, Cagri G.
Abstract : Purpose: To present peripheral retinal vasculopathy and foveal ellipsoid zone abnormalities as novel fundus manifestations of Cockayne syndrome (CS), a rare autosomal recessive condition with well-described ophthalmic associations. Methods: Clinical examination, wide-field fundus photography, wide-field fundus autofluorescence, wide-field fluorescein angiography, and spectral domain optical coherence tomography (SD-OCT) were used to diagnose and document the patient's clinical presentation. Results: Our patient presented with postnatal growth delay, neurologic dysfunction, premature aging, dental anomalies, sensory neural hearing loss, and pigmentary retinopathy. This constellation of clinical features satisfies the clinical diagnostic criteria of CS Type 1. In addition to these well-known features, we used multimodal retinal imaging to perform an in-depth analysis of the retinal manifestations of CS and report peripheral vasculopathy and ellipsoid zone abnormality as two novel features which have not previously been described in conjunction with CS. Conclusion: This case report is intended to assist physicians in making the correct diagnosis of this rare condition by reviewing the clinical diagnostic criteria and providing the most comprehensive fundus imaging of CS available in the literature to date. Abstract : This case report demonstrates novel retinal findings associated with Cockayne Syndrome, a rare autosomal recessive condition. Through multimodal retinal imaging, we provide evidence of peripheral retinal vasculopathy and present the most complete fundus imaging characteristics of Cockayne Syndrome reported in the literature.